基于三坐标的弧齿锥齿轮齿面误差测量与评定 - 赵华 (Jixie chuandong)
A method of spiral bevel gear tooth surface error measurement and evaluation based on three-coordinate measurement is given according to the characteristics of spiral bevel gear.The 3D solid model building in UG is regarded as the gear ideal factor of measure and error evaluation;the grid nodes in the real gear tooth surface are measured by using three-coordinate measurement machine,and the collected data point is led into UG.The tooth surface error of spiral bevel gear is reflected by the difference surface which is fitted by the deviation between real tooth surface and theoretical tooth surface.The effectiveness and feasibility of this method is verified by actual measuring and evaluating the automobile rear axle driven gear.